2013
DOI: 10.1063/1.4788924
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrocaloric measurements of a multilayer capacitor using scanning thermal microscopy and infra-red imaging

Abstract: We present two techniques for directly measuring electrocaloric temperature change in a multilayer capacitor based on BaTiO3. Scanning thermal microscopy with resolution 80 mK, and infra-red imaging with resolution 25 mK, each record electrocaloric temperature changes of ∼0.5 K that match within error. We find that scanning thermal microscopy is more suitable for detecting giant electrocaloric effects in thin films with substrates present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
77
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 16 publications
5
77
1
Order By: Relevance
“…C The discovery one decade ago of giant electrocaloric (EC) effects near ferroelectric phase transitions in ceramic thin films, 1 and then in thicker films of polymers, 2 triggered intense research into ferroelectric materials for environmentally friendly EC cooling. [3][4][5][6] Although there have been significant advances in materials developments, [7][8][9] measuring techniques, [10][11][12][13][14][15][16] and heat-pump prototypes, [17][18][19][20][21] the commercial application of EC materials remains elusive. The main obstacle is that EC performance is limited by breakdown field, while another major obstacle is that electric-fieldinduced strain produces mechanical fatigue and ultimately failure.…”
mentioning
confidence: 99%
“…C The discovery one decade ago of giant electrocaloric (EC) effects near ferroelectric phase transitions in ceramic thin films, 1 and then in thicker films of polymers, 2 triggered intense research into ferroelectric materials for environmentally friendly EC cooling. [3][4][5][6] Although there have been significant advances in materials developments, [7][8][9] measuring techniques, [10][11][12][13][14][15][16] and heat-pump prototypes, [17][18][19][20][21] the commercial application of EC materials remains elusive. The main obstacle is that EC performance is limited by breakdown field, while another major obstacle is that electric-fieldinduced strain produces mechanical fatigue and ultimately failure.…”
mentioning
confidence: 99%
“…[36][37][38][39] In particular, the electrocaloric properties of BTO thin films have been intensively investigated. 12,18,19,26,[40][41][42][43][44][45][46][47] Interestingly, it was reported that applying a uniaxial compressive stress could enhance and widen the electrocaloric response considerably in ultrathin BTO films due to tuning of the depolarization field. 26 It is also reported that the electrocaloric peak under tensile stresses moves towards higher temperatures with its magnitude slightly enhanced in BTO single crystals.…”
mentioning
confidence: 99%
“…In the case of bulk materials, the traditional approach to measuring this quantity is to measure either the change in temperature using thermometry [18] or the heat flux using calorimetry. [19,20] Similar to the PEE, the last few decades have seen growing interest in investigating the ECE in thin films and, in turn, a need for more advanced measurement approaches has developed.…”
Section: Introductionmentioning
confidence: 99%